The Growth of White-Collar Unionism and Public Policy in Canada - Sayers Bain, Georges (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
The number of white-collar workers is rapidly increasing. If the trade union movement is to continue to play an effective role in the industrial relations system, it must recruit these workers. But so far, outside of the public sector of the economy, there is relatively little white-collar unionism in Canada. The major reason for this is that Canadian public policy on industrial relations is not very effective in curbing management opposition to white-collar unionism. The paper suggests several ways in which public policy might be made not only more effective in this regard but also deals with the problems arising from the growth of white-collar unionism.